THE ANALYSIS OF SOIL STRUCTURE INTERACTION EFFECTS IN FOUNDATION AND BASEMENT ON AMPLIFICATION FACTOR OF SURFACE RESPONSE SPECTRA - NENGAH SUKERTHA (NIM 25005003), I
The determination of earthquake dynamic load depends on the propagation of seismic wave from the base rock to the surface through free-field soil medium. In real condition, especially on high-rise buildings, there are buried structures such as foundation and basement. The dynamic analysis of the buried structures was done by numerical method of Plaxis Dynamics version 8.2 software based on finite element method in time domain and 2 (two) dimensional analysis verified using Deepsoil version 6.2 software which is based on time domain and 1 (one) dimensional analysis. The research was done on 62 cases involving any conditions such as free-field soil condition, soil-structure interaction condition related to buried structures such as basement and foundation, and soil-structure interaction condition related to both buried structures and upper structures (high-rise building, 5 (five) floors), varied with stiff, medium and soft site classification and variation in Peak Base Acceleration (PBA) of 0.1 g, 0.2 g and 0.3 g for shallow crustal and subduction earthquake mechanism. The determination of ??and???Rayleigh damping coefficients is one of the interesting topics that is discussed in this research. The ??and?? parameters are the input motion in time domain analysis by Plaxis Dynamics version 8.2. The ??and?? parameters are determined by Deepsoil version 6.2 software. The results of the analysis are response spectra and envelope response spectra, which are compared to the recent design standard such as UBC (Uniform Building Code) 1997 and SK SNI 1726 – 2002. The buried structures condition analysis has shown that smaller value of Peak Ground Acceleration (PGA) varies between 0% to 12.5% compared to that of the free-field condition for peak base acceleration of 0.1 g, 0.2 g and 0.3 g, under soft, medium and stiff site classification. The dimentional variation in foundation diameters look does not give any effects on the earthquake wave propagation to the surface.